Arketipe tokoh utama dalam novel Unit Gaib Darurat karya Tim Kisah Tanah Jawa: Kajian psikologi Carl Jung - Khusnul Sri Ainunnisa; Rina Ratih Sri Sudaryani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
The personality of characters in literary works does not merely reflect social reality but also demonstrates the complex inner dynamics of human beings. Such complexity is evident in the main character of the novel Unit Gaib Darurat by the Tim Kisah Tanah Jawa, who exhibits various archetypes and personality-shaping factors. This study describes the archetypes of the main character as well as the factors influencing the structure of their personality. This research applies a descriptive qualitative method through an objective approach. The data consist of excerpts from the novel containing archetypes and personality-forming factors. The data analysis process includes stages of collection, reduction, presentation, and conclusion drawing, with validity testing conducted through theory and source triangulation. The results show 45 data points of archetypes, comprising Persona (11 data), Anima (8 data), Shadow (18 data), and Self (8 data). The Shadow is the most dominant archetype, depicting the character's dark side and inner burdens. Additionally, 33 data points of personality factors were found, with the environment being the dominant factor influencing the character's perspective and emotional responses. These findings confirm that the dynamics of a character's personality are formed through the interaction between psychological structures and life experiences within the narrative.